The effects of repetitive transcranial magnetic and transcranial direct current stimulation on memory functions in older adults with mild cognitive impairment: a systematic review and meta-analysis - Hu, Mengdie; Nitsche, Michael A.; Lv, Yanxin; Han, Hairong; Lin, Xu; Qi, Fengxue (Frontiers in Human Neuroscience, 2024)
Mild cognitive impairment (MCI) is a condition that impairs activities of daily living, and often transforms to dementia. Repetitive transcranial magnetic stimulation (rTMS) and transcranial direct current stimulation (tDCS) show promise in improving cognitive functions in MCI patients. In this meta-analysis, we aimed to compare the effects of rTMS and tDCS on memory functions in MCI patients. We explored eight databases from their inception to March 16, 2024. We obtained 11 studies with 406 patients with MCI. We used the standardized mean difference (SMD) with a 95% confidence interval (CI) to synthesize the effect size. rTMS and tDCS significantly improved memory functions in MCI patients (SMD = 0.61; 95% CI: 0.41-0.82; P < 0.00001; I 2 = 22%). In subgroup analysis of number of stimulation sessions, both rTMS and tDCS over 10 sessions (SMD = 0.84; 95% CI: 0.50 -1.17, P < 0.00001, I 2 = 0%) significantly improved the memory function in MCI patients. The subgroup analyses on different stimulation types (SMD = 0.78; 95% CI: 0.51-1.06; P < 0.00001; I 2 = 0%) and treatment persistent effects (SMD = 0.93; 95% CI: 0.51-1.35, P < 0.0001, I 2 = 0%) showed that rTMS was more effective than tDCS. rTMS with a stimulation frequency of 10 Hz (SMD = 0.86; 95% CI: 0.51-1.21; P < 0.00001; I 2 = 0%) and over 10 sessions (SMD = 0.98; 95% CI: 0.58-1.38; P < 0.00001; I 2 = 0%) at multiple sites (SMD = 0.97; 95% CI: 0.44-1.49; P = 0.0003; I 2 = 0%) showed a great improvement in the memory performance of patients with MCI. rTMS was more likely to appear temporary side effects (risk ratio (RR) = 3.18, 95% CI: 1.29-7.83, P = 0.01). This meta-analysis suggests that rTMS and tDCS are safe and efficient tools to improve memory functions in patients with MCI, while rTMS had a larger effect than tDCS. rTMS with a stimulation frequency of 10 Hz targeted on multiple sites over 10 sessions showed the greatest effect. We could not conclude parameters of tDCS because of insufficient data.